Ground-based walking training improves quality of life and exercise capacity in COPD - Wootton, S.; Ng, C.; McKeough, Z.; Jenkins, Susan; Hill, Kylie; Eastwood, Peter; Hillman, D.; Cecins, Nola; Spencer, L.; Jenkins, C.; Alison, J. (European Respiratory Society, 2014)
This study was designed to determine the effect of ground-based walking training on health-related quality of life and exercise capacity in people with chronic obstructive pulmonary disease (COPD). People with COPD were randomised to either a walking group that received supervised, ground-based walking training two to three times a week for 8–10 weeks, or a control group that received usual medical care and did not participate in exercise training. 130 out of 143 participants (mean±SD age 69±8 years, forced expiratory volume in 1 s 43±15% predicted) completed the study. Compared to the control group, the walking group demonstrated greater improvements in the St George’s Respiratory Questionnaire total score (mean difference -6 points (95% CI -10– -2), p<0.003), Chronic Respiratory Disease Questionnaire total score (mean difference 7 points (95% CI 2–11), p<0.01) and endurance shuttle walk test time (mean difference 208 s (95% CI 104–313), p<0.001). This study shows that ground-based walking training is an effective training modality that improves quality of life and endurance exercise capacity in people with COPD.